Short Term Outcome and Associated factor Among Stroke Patien Given Trombolysis - Bentrez, Florilyn Joyce C (Universitas Muhammadiyah Surakarta, 2025)
The study aimed to investigate the short-term outcome and associated factors among acute ischemic stroke patients given rTPA (Recombinant tissue plasminogen activator). This is a hospital-based cross-sectional retrospective study among 107 acute stroke patients given rTPA for a span of 3 years. A favorable outcome is defined as the modified Rankin Scale (MRS) 0 to 2, while a score > 2 is defined as a poor outcome. Mortality and adverse events were also documented. The majority (57%) had favorable outcomes on discharge. Initial stroke severity, stroke etiology, and presence of symptomatic Intracerebral hemorrhage (ICH) were significant factors for discharge outcome. There was no significance as to age group and as to needle time of 0-3 hours versus 3-4.5 hours. The symptomatic ICH rate is 5.6%. The overall mortality rate is 15.88% (47% due to malignant infarction, 17.6% due to symptomatic intracerebral hemorrhage (sICH), 23.52% due to basilar artery occlusion (BAO), and 11.7% due to medical causes). With a dose of 0.6mg/kg, our data indicate favorable discharge outcomes of thrombolysis. A high baseline NIHSS, cardioembolic stroke etiology, and the presence of sICH are seen in patients with poor outcomes. The rate of sICH is consistent with other literature, however with high mortality (100%). Overall mortality is high primarily due to malignant infarct. Institutions must be capacitated to address outcomes and complications of thrombolysis.